The Analysis of students’ higher order thinking skills (HOTS) in Wave and Optics Using IRT with Winstep Software - Soeharto Soeharto; Rosmaiyadi Rosmaiyadi (Journal of Educational Science and Technology (EST), 2018)
This study aims to determine the Descriptions of Student Higher Order Thinking Skills (HOTS) of Singkawang STKIP physics education students. In addition, this research also aims to. This research is quantitative descriptive. Validity and reliability tests in this study will use rasch modeling with the help of Winsteps software. Through this research will be obtained the exposure of HOTS data of Singkawang STKIP physics education students on wave and optical material so that it is expected to be the basis for further research. In this research, HOTS description of students is produced, namely: (1) HOTS students at the highest ability are owned by LD02 (measure = +2.56 logit) to the lowest ability possessed by LD09 (measure = -2.42) with a standard level of difficulty of the problem with a logit value of 0.48 (2) most students experience difficulties when formulating the physics equation and the calculation process (3) analyzing is the ability that is most dominated by students with logit values in a row of - 0.71 and -0.67 followed by creative ability with logit values of -0.12 and -, 028, respectively, the ability to evaluate with logit values of 0.00, 0.95 and 0.82, respectively. , (4) item reability is a matter of 0.71 (Reliable good category), (4) the ability of students is low as 0.12 means that the HOTS students are low.